Multimodal assessment of biometric changes in injection sites and physiology and behavior in beef calves receiving two different clostridial immunizations compared to negative controls - White, Bradley J.; Anderson, David E.; DuCharme, Alecia; Miesner, Matt D.; Larson, Robert L.; Amrine, David (My University, 2013)
Clostridial immunizations are commonly administered to cattle, and understanding the physiologic and behavioral effects of vaccination may influence preventative health program design. A randomized, controlled, blinded clinical trial was conducted using multimodal assessment of injection sites, physiologic, and behavioral changes in calves receiving one of two clostridial vaccinations and negative controls. Calf response after injection was monitored daily utilizing physiologic parameters (rectal temperature, pulse, respiratory rate, and body weight), measurements of injection site reaction (lesion surface area, depth, and volume), skin surface temperature (thermography), and avoidance response to pressure at injection site (algometer). Calf behavior was remotely monitored using pedometers, accelerometers, and a remote triangulation system. Calves vaccinated with the clostridial products had larger injection site lesions and greater injection site surface temperature ratios compared to saline controls. The pressure required to stimulate a reaction differed among treatments and this effect was modified by treatment group with control calves requiring more pressure to stimulate avoidance response early in the trial. The percent of time calves spent standing was greater in one of the vaccine groups relative to controls as measured by the accelerometers. The location monitoring system revealed differences among treatment groups relative to time spent at the hay and grain feeding areas. This research illustrates that clostridial vaccination induced multiple changes in injection site, physiological, and behavioral variables as compared to negative controls. The biometric profile generated by the combination of multimodal assessment tools employed in this project demonstrates the advantages of objective assessment to describe effects of vaccine administration.
Keywords: Cattle; Behavioral monitoring; Clostridial vaccine; Vaccine reaction